1793-1993: terror, violence, the power of words (1993)
"From trauma to conflict". The signifiers in the title of this paper enable the author to develop the axes around which this symposium turned. 1973 witnessed the first use of terror to impose the legitimacy of the ideology it preached. 1993 saw the return of a nationalist movement in which violence seemed to have given way to terrorism. It is preferable for the first named to reign in order to elude terror and to eventually open up a space for the reinscription of the process of symbolization. This is the thematic axis of this proposal to reconsider the powers of psychoanalytic discourse in the examination of the present historical juncture.